Effect of Pomegranate Seed Extract on Free Radical Damage and Antioxidant Activity Under Cisplatin-Induced Oxidative Stress Conditions in Rabbit Testes - Benzer, F.; Kandemir, F. M.; Yildirim, N. C.; Ozan, S. T. (Asian Journal of Chemistry, 2011)
The aim of this study is to evaluate the protective effect of pomegranate seed extract on cisplatin-induced oxidative stress in rabbits testes. Rabbits were divided into three groups; (i) being control group, (ii) cisplatin group and (iii) cisplatin + pomegranate seed extract group. The level of malondialdehyde and glutathione, the activity of catalase, glutathione peroxidase, were measured in testes tissue of rabbits. Malondialdehyde levels were increased depending on cisplatin. In the case of cisplatin + pomegranate seed extract, malondialdehyde levels were found to be lower than cisplatin group (p < 0.05). In cisplatin group, catalase, glutathione peroxidase activity and glutathione levels were decreased when compared to control but in cisplatin + pomegranate seed extract group, catalase, glutathione peroxidase activity and glutathione levels were found higher than cisplatin group (p < 0.05). The pomegranate seed extract supplementation may play a protective role or decrease the side effects of cisplatin-induced testes toxicity from cancer medicines.
Keywords: Pomegranate; Cisplatin; Testes; Rabbit; Antioxidants